Integrated Communication as Strategic Communication - Adriana GRIGORESCU; Maria-Magdalena LUPU (Revista de Management Comparat International)
Between any form of communication there is an unbreakable connection that can lead to the improvement of the organizational competences because communication remains one of the basic activities with a great influence on agencies, groups, communities and environments. The communication in successful organizations is clearly the integrated one. Integrated communication could only be successful when included and subordinated to the global organizational strategy and requires careful planning and coordinated efforts. This is the easiest way to explain the title of this work as the result of a sustained effort of studying this concept. Integrated communication is still little known, too little recognized and used and the advantages of this type of communication are neglected most of the time in small and average organizations. This statement has been demonstrated especially by being adopted by all great corporations. The present work presents in its second half the results of a research made last year regarding the situation of the integrated communication in the organizations of south Romania. The aim of this research is to identify the results of applying this concept.